The Role of the Sociopreneurial Environment and Independent Attitude in Enhancing the Business Development of Street Vendors at the Taman Jomblo Tourism Area, Kota Baru Jambi (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the influence of sociopreneur environment and independent attitudes on the development of street vendor businesses in the Taman Jomblo Tourism area, Kota Baru, Jambi. This study uses a quantitative approach with a survey method. The study population is all street vendors operating in the area as many as 136 traders, with sampling techniques using saturated sampling (census). Data were collected through questionnaires measured using the Likert scale and analyzed using multiple linear regression. The results of the study show that the sociopreneur environment has a positive and significant effect on the business development of street vendors. An independent attitude also has a positive and significant effect on the development of street vendors' businesses. In addition, the results of simultaneous tests showed that the sociopreneur environment and independent attitude together had a significant effect on the business development of street vendors. The value of the determination coefficient shows that most of the variation in business development can be explained by these two variables, while the rest is influenced by other factors outside the research model. This study concludes that the business development of street vendors is not only influenced by internal factors of business actors, but also by the supportive social environment. Therefore, efforts are needed to strengthen the sociopreneur environment and increase the independent attitude of street vendors to encourage business sustainability in tourist areas.